KSU Swine Enterprise Record program - Langemeier, Michael R.; Goodband, Robert D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
On January 1, 1991, a enterprise record program was implemented on 13 swine operations in Kansas. The program evaluates economic criteria in the areas of variable and fixed costs, labor, marketing, and production and is conducted in cooperation with extension specialists and swine producers in Kansas, Nebraska, and South Dakota. Every six months, producers' records are summarized, and the data are pooled to form state and regional averages. This data base is then divided into the top, middle)and bottom third of producers based solely on profit per cwt. of pork produced. This summary allows producers to compare their individual records to those of other swine operations and identify strengths and weaknesses in their operation. In addition, it also identifies the criteria that may have the greatest impact on profitability. The Kansas Swine Enterprise Records Program is an opportunity for producers who have never kept records to evaluate the profitability of their operations. It also allows producers who keep detailed biological records of their operations an opportunity to assess their financial profitability. In either case, records can establish a baseline level of production and profit in order to make sound management decisions.
Typo of author's name M. L. Langemeier; should be M. R. Langemeier.
Keywords: Swine; Enterprise; Records; Analysis; Profitability